ICT and its influence on psychosocial development - Guzmán Huayamave, Kennya (2020)
This article describes the value of Information and Communication Technologies (ICT) as a teaching resource that opens up opportunities for knowledge development. Being immersed in a society that children are digital natives, the teacher needs to incorporate technology in their educational processes in order to enhance the psychosocial development of their students. In this context, the research aims to promote spaces for reflection so that pedagogical scenarios are increasingly interactive with the knowledge and socialization of peers in the “Camino al Espacio” school in the city of Guayaquil. From this perspective, qualitative-quantitative techniques with a descriptive and exploratory character were used. The methodology considered was: observation, interview and survey. In conclusion, the teaching performance must assume in its formation the topic of ICT and in this approach, rethink the experiences that are built in the teaching process.